Value of robotic surgery simulation for training surgical residents and attendings: a systematic review protocol - Ngan Nguyen; Kathryn K Howard; Hussein Makki; Nathan M Novotny; Misa Mi (BMJ Open)
Introduction Robotic surgery is a method of minimally invasive surgery performed through small incisions using a remote robotic console. Surgical residents and attendings participate in simulation training to be able to effectively perform robotic surgery using wet labs, dry labs and virtual reality platforms. Our objective is to identify the effectiveness of robotic simulation on novice robotic surgeons. This review will answer our review question: To what extent are robotic simulations for training novice robotic general surgery residents and attendings associated with improved outcomes in comparison with no simulation training?Methods and analysis A comprehensive search of PubMed, Embase, the Cochrane Library and Web of Science was performed. The studies were then determined to meet initial screening criteria by one individual for abstract and title with full text screening performed by two authors independently and in duplicate. Narrative themes will be collected, analysed and summarised where possible.Ethics and dissemination There is no Institutional Review Board approval required given that the work is carried out on previously published papers. The final manuscript and results will be presented and published at an academic conference and peer -reviewed journal.PROSPERO registration number CRD42021274090.